Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fphar.2023.1152672
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of exosomal non-coding RNAs in breast cancer drug resistance, focusing on underlying molecular mechanisms

Abstract: Breast cancer (BC) is the most common malignancy among women worldwide. Like many other cancers, BC therapy is challenging and sometimes frustrating. In spite of the various therapeutic modalities applied to treat the cancer, drug resistance, also known as, chemoresistance, is very common in almost all BCs. Undesirably, a breast tumor might be resistant to different curative approaches (e.g., chemo- and immunotherapy) at the same period of time. Exosomes, as double membrane-bound extracellular vesicles 1) secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 289 publications
(317 reference statements)
0
6
0
Order By: Relevance
“…The exosomal lncSENP3-EIF4A1 exhibits reduced expression in HCC patients compared to healthy controls [11]. Both in vitro and in vivo studies have demonstrated that the introduction of SENP3-EIF4A1 functions as a tumor suppressor, inhibiting the proliferation and migration of HCC cells and acting as a competitor of the miR-9-5p target [114].…”
Section: Lncrna-extracellular Vesicles As Biomarkers In Hepatocellula...mentioning
confidence: 99%
See 1 more Smart Citation
“…The exosomal lncSENP3-EIF4A1 exhibits reduced expression in HCC patients compared to healthy controls [11]. Both in vitro and in vivo studies have demonstrated that the introduction of SENP3-EIF4A1 functions as a tumor suppressor, inhibiting the proliferation and migration of HCC cells and acting as a competitor of the miR-9-5p target [114].…”
Section: Lncrna-extracellular Vesicles As Biomarkers In Hepatocellula...mentioning
confidence: 99%
“…Subsequently, early endosomes integrate active molecules and other substances forming multiple intraluminal vesicles (ILVs). Late endosomes mature into multivesicular bodies (MVBs), which can encapsulate cargoes derived from various organelles, including the trans-Golgi network (TGN) and endoplasmic reticulum (ER) compartments [11]. Subsequently, MVBs can fuse with lysosomes [12], and their content becomes degraded; some degradation products, such as amino acids, are made available for reuse by the cell.…”
Section: Introductionmentioning
confidence: 99%
“…EVs contribute to tissue repair and regeneration and immunosurveillance. Subtypes of EVs are microvesicles, exosomes, and apoptotic bodies, which are classified depending on their biogenesis, release pathways, and size ( Samanta et al, 2018 ; Rezaee et al, 2023 ). EVs derived from different types of cells promoted functional recovery after SCI through their neuroprotective and neuroregenerative properties ( Romanelli et al, 2019 ).…”
Section: Using Cell-derived Evs For the Regeneration Of Scimentioning
confidence: 99%
“…EV-mediated transfer of ncRNAs from resistant cancer cells to sensitive cells is an important mechanism for propagation of tumour drug resistance. This topic has been reviewed deeply, in a 2021 systematic review exploring the role of EV-carried miRNAs in the induction of chemoresistance in multiple cancer types [ 125 ], and in recently published BC focused reviews by Weon Yi [ 126 ] and Rezaee et al [ 127 ].…”
Section: The Role Of Ncrnas In Breast Cancermentioning
confidence: 99%